KEJADIAN HIPERTENSI PADA ANAK DAN REMAJA DENGAN STATUS GIZI OBESITAS - Lailatun Nimah (Jurnal Ilmiah Kesehatan Media Husada, 2019)
Introduction: The incidence of hypertension in children and adolescents can not be explained. Methods: This research is a correlative descriptive with research population of children and adolescents with nutritional status in elementary, junior and senior high school in Surabaya. The sample was 113 people, used consecutive sampling. The independent variable is obesity nutritional status of children and adolescent, while dependent variable is hypertension in child and adolescent. Data analysis with Chi Square for nutritional status variables and hypertension. The standard nutritional status variables using height measuring instruments and calibrated scales to obtain the status of child and adolescent nutritional data are adjusted to the 2007 WHO standards required by Ministry of health Republik Indonesia 2010. The hypertension variable of research using digital oscillometric.Results: Blood pressure measuremented data is sistole value, most of which is hypertension level II. The results of diastolic data are mostly in the prehypertension category. Conclussion:The incidence of hypertension in children and adolescents in Surabaya is boys bigger than women. The sistole value in blood pressure in children and adolescents with the most obesity is hypertension level II. Diastole values in blood pressure with the most obesity is prehypertension. Key words: Hypertension, Obesity, Children, Adolescent